ANALISIS KUALITAS LAYANAN DENGAN MENGGUNAKAN E- SERVICE QUALITY UNTUK MENGETAHUI KEPUASAN PELANGGAN BELANJA ONLINE TOKOPEDIA - Rosa, Mila; Sumowo, Seno; Puspitadewi S, Ira (Jurnal Ilmu Manajemen Retail Universitas Muhammadiyah Sukabumi, 2023)
The development of the internet in the world is getting wider so that many companies are trying to create products and services to meet the wants and needs of the community. Companies must create new marketing strategies in order to survive and attract larger consumers. This study aims to determine the effect of service quality using e-service quality on shopping customer satisfaction at Tokopedia. The population in this study are Tokopedia consumers. The number of samples used is 150 respondents and selected by purposive sampling and data collection methods through questionnaires. The analytical tool used in this research is the SPSS 18.0 program. The results of this study show that efficiency (x1), privacy (x2), fulfillment (x3), site aesthetic (x4), responsiveness (x5) and easy of use (x6) have a positive and significant effect on customer satisfaction (Y). The process that has the most influence on improving the quality of Tokopedia's online shopping services is the improvement of service quality which affects the customer as a determinant of success in customer satisfaction.